2022
DOI: 10.3390/vaccines10050670
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance or Rejection of the COVID-19 Vaccine: A Study on Iranian People’s Opinions toward the COVID-19 Vaccine

Abstract: We aimed to assess the Iranian people’s attitude and confidence in the COVID-19 vaccine, their concerns about the safety of vaccines, and their reasons for accepting or rejecting the COVID-19 vaccine. We conducted a web-based cross-sectional study with a mixed qualitative–quantitative approach from December 2020 to February 2021. Our questionnaire consisted of a COVID-19 vaccine attitude questionnaire, a COVID-19 vaccine confidence inventory, a modified vaccine safety scale, and questions about participants’ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…However, only one study was conducted in each of the following countries; Republic of Congo ( 59 ), Japan ( 60 ), Poland ( 10 ), Cameroon ( 7 ), Israel ( 61 ), Mexico ( 62 ), Malta ( 63 ), Scotland ( 6 ), Indonesia ( 64 ), England ( 65 ), South Korea ( 66 ), Iran ( 67 ), Nigeria ( 68 ), Tunisia ( 69 ), Netherlands ( 70 ), Thailand ( 71 ), Vietnam ( 72 ), United Arab Emirates ( 73 ), Botswana ( 74 ), Sudan ( 75 ), Czechia ( 76 ), Uganda ( 77 ), France ( 78 ), and in Egypt ( 79 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, only one study was conducted in each of the following countries; Republic of Congo ( 59 ), Japan ( 60 ), Poland ( 10 ), Cameroon ( 7 ), Israel ( 61 ), Mexico ( 62 ), Malta ( 63 ), Scotland ( 6 ), Indonesia ( 64 ), England ( 65 ), South Korea ( 66 ), Iran ( 67 ), Nigeria ( 68 ), Tunisia ( 69 ), Netherlands ( 70 ), Thailand ( 71 ), Vietnam ( 72 ), United Arab Emirates ( 73 ), Botswana ( 74 ), Sudan ( 75 ), Czechia ( 76 ), Uganda ( 77 ), France ( 78 ), and in Egypt ( 79 ).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have tried to evaluate attitude and willingness toward the COVID‐19 vaccine. In total, attitude toward vaccination against COVID‐19 among Iranian has been reported positive regardless of the vaccine type, from about 70% acceptance rate to more than 80% acceptance rate, which is slightly more than the global willingness 23–27 . Reportedly, misinformation and lack of knowledge contribute to hesitancy and negative attitudes toward COVID‐19 vaccination 23,28,29 …”
Section: Introductionmentioning
confidence: 99%
“…In total, attitude toward vaccination against COVID-19 among Iranian has been reported positive regardless of the vaccine type, from about 70% acceptance rate to more than 80% acceptance rate, which is slightly more than the global willingness. [23][24][25][26][27] Reportedly, misinformation and lack of knowledge contribute to hesitancy and negative attitudes toward COVID-19 vaccination. 23,28,29 Due to the extensive mortality of COVID-19, the health authorities approved emergency administration of the COVID-19 vaccines worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in Turkey showed that most of the study participants (66.1%) refused to receive foreign vaccines and were typically willing to receive domestic vaccines [8]. A study on 1928 participants in Iran showed that 69% of the participants were willing to receive vaccines, and female gender, lower educational attainment, and loss of relatives due to COVID-19 infection were signi cantly related to the negative attitudes regarding vaccination [9]. Abbasi et al showed that only a small number of Iranian people with multiple sclerosis were hesitant against COVID-19 vaccination (6.9%), while the majority accepted vaccination [10].…”
Section: Introductionmentioning
confidence: 99%